A rare cause of primary adrenal insufficiency due to a homozygous Arg188Cys mutation in the STAR gene. (21st March 2018) - Burget, Lukas; Parera, Laura Audí; Fernandez-Cancio, Monica; Gräni, Rolf; Henzen, Christoph; Flück, Christa E
Summary: Steroidogenic acute regulatory protein ( STAR ) is a key protein for the intracellular transport of cholesterol to the mitochondrium in endocrine organs (e.g. adrenal gland, ovaries, testes) and essential for the synthesis of all steroid hormones. Several mutations have been described and the clinical phenotype varies strongly and may be grouped into classic lipoid congenital adrenal hyperplasia (LCAH), in which all steroidogenesis is disrupted, and non-classic LCAH, which resembles familial glucocorticoid deficiency (FGD), which affects predominantly adrenal functions. Classic LCAH is characterized by early and potentially life-threatening manifestation of primary adrenal insufficiency (PAI) with electrolyte disturbances and 46, XY disorder of sex development (DSD) in males as well as lack of pubertal development in both sexes. Non-classic LCAH manifests usually later in life with PAI. Nevertheless, life-long follow-up of gonadal function is warranted. We describe a 26-year-old female patient who was diagnosed with PAI early in life without detailed diagnostic work-up. At the age of 14 months, she presented with hyperpigmentation, elevated ACTH and low cortisol levels. As her older brother was diagnosed with PAI two years earlier, she was put on hydrocortisone and fludrocortisone replacement therapy before an Addisonian crisis occurred. Upon review of her case in adulthood, consanguinity was noted in the family. Genetic analysis for PAI revealed a homozygous mutation in the STAR gene (c.562C>T, p.Arg188Cys) in both siblings. This mutation has been previously described in non-classic LCAH. This case illustrates that early onset, familial PAI is likely due to autosomal recessive genetic mutations in known genes causing PAI. Learning points: In childhood-onset PAI, a genetic cause is most likely, especially in families with consanguinity. Adult patients with an etiologically unsolved PAI should be reviewed repeatedly and genetic work-up should be considered. Knowing the exact genetic diagnosis in PAI is essential for genetic counselling and may allow disease-specific treatment. Young men and women with NCLAH due to homozygous STAR Arg188Cys mutation should be investigated for their gonadal function as hypogonadism and infertility might occur during puberty or in early adulthood.